KATA-KATA SLANG DALAM INSTAGRAM - ANIS, PETRANIA T. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT  This research which is entitled ‘Slang Words on Instagram’ is an attempt to identify the types,kinds and forms also to analyze the meanings of slang words on instagram. The theories used in this research are by Patridge and Bloomfield’s theories and the data will be taken from instagram. This research applies a descriptive method. Theoretically, this research will give a contribution to linguistic study especially on sociolinguistic field more specifically on slangs found in instagram and also provide with rich information about slang. Practically, this study can help students and readers in understanding the types, forms and meanings of slang words in instagram. The result shows that types and form of slang found in instagram are abbreviation, shortened forms, facetious misprounanciation, public house slang, society slang and the meanings found in instgaram used online dictionary. Keywords : Slang words, instagram, Descriptive Analysis